Changes in erythropoietin and haematological adaptation at moderate altitude training - Nomura, T.; Mankyu, H.; Asano, K.; Tomura, S. (Japan Journal of Mountain Medicine, 1994)
Thirteen well-training male swimmers trained for 14 days at 1,892m. Blood samples for haemoglobin (Hb), haematocrit concentration (Ht), red blood cell counts (RBC), mean red cell volume (MCV), erythropoietin (EPO), reticulocyte, ferritin, iron (Fe), 2-3DPG were determined pre-, during and post-altitude exposure. The RBC counts increased 8th and 12th day during altitude. MCV decreased significantly during and post-altitude compared to pre-altitude. The EPO increased significantly (+40%) during 4th and 8th day in altitude, but normalized after 12th day. The reticulocyte counts had increased significantly above pre-altitude values (+18%) at post-altitude. 2-3DPG increased significantly on day 14 of post-altitude. These findings indicate that the erythropoietic response to the moderate altitude training was not sufficient to improve AT in spite of changes in haematological adaptation. However, swimming performance significantly improved (69.2% of all the swimmers made best record).